Funding liquidity on bank lending growth: The case of India - Erum Shaikh; Muhammad Nawaz Tunio; Vishal Dagar (Journal of Entrepreneurship, Management and Innovation)
PURPOSE: By bridging the funding gap between funding surplus units and deficit units, financial institutions like banks play a crucial role in fostering economic development in a nation. Banks provide the crucial task of organizing individual and institutional resources and directing them to those prepared to engage in business ventures or other productive uses. The aim of this paper is to evaluate the relation between funding liquidity and bank lending growth (BLG). An empirical analysis between bank capital and the funding liquidity ratio on bank lending growth (BLG) using the generalized method of moments (GMM) approach for the sustainable business has been not identified before. Therefore, this study tries to fill this gap. METHODOLOGY: The data was collected from 59 commercial banks in India from 2010 to 2022 which comprises of 21 public sector banks, 18 private sector banks, and 20 foreign banks. The GMM approach was what we employed. This strategy is typically utilized in situations in which the distribution of the data is uncertain and there is a concern with over identification. GMM offers a consistent, asymptotically normal, and efficient estimator in comparison to all of the other estimators that merely use the information presented by the moment conditions. FINDINGS: Findings suggests that there is a significantly negative influence of bank capital and funding liquidity on bank lending. This indicates that higher capital can limit the effect of funding liquidity on the growth of the banks’ loans, therefore the findings are consistent with the hypothesis that higher capital can lower the effect of funding liquidity. This study’s model also reveals the significantly favorable impact that funding liquidity has on the expansion of banks’ loan portfolios, which ultimately results in a more sophisticated increase in the growth rate of bank lending. IMPLICATIONS: This can be an importance piece of information for policy makers in taking accurate decisions to induce the BLG in the presence of an interactive association of funding liquidity and the lending growth rate at different capital levels. We found that the banks’ lending growth rate is significantly influenced by its past values with a significant p-value of less than 1%. The findings imply that capital funds and liquidity funds support the BLG rate in India by strengthening and neutralising the risk involved and absorbing the losses generated by stressed assets. ORIGINALITY AND VALUE: This study makes a significant contribution to the creation of a more in-depth understanding of the potential relationship between banks’ funding liquidity, capital funds, and bankers’ lending behavior, in particular with reference to developing market nations like India.